EFFECTIVENESS OF GOW-GATES AND INFERIOR ALVEOLAR NERVE BLOCKS IN INDUCING ANAESTHESIA IN PATIENTS UNDERGOING FULL MOUTH REHABILITATION - RupawatDivya Kamlesh; Dhanraj Ganapathy; Sanjana Devi N; Minal Gopal Tulsani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Tooth preparation involves aggressive removal of enamel and dentin. The pressure applied during tooth preparation and the thermal trauma induced can stimulate the free nerve endings in the dentino enamel junction and can transmit pain subsequently. The purpose of this study is to evaluate the efficacy of anaesthesia between Inferior alveolar nerve block and GowGates mandibular block nerve blocks. To evaluate effectiveness of Gow gates and inferior alveolar nerve blocks in inducing anaesthesia in patients undergoing full mouth rehabilitation. 50 patients undergoing fmr treatment were selected based on the inclusion and exclusion criteria.The effectiveness of IANB and GGMB nerve blocks were evaluated by the parameters of pain (vas scale) , discomfort (vas scale) and response to electric pulp tester. The discomfort and pain levels were slightly higher with IANB block and the response to pulp tester was more with GGMB block. The p values were not significant. The results showed that there is no significant difference in anaesthesia obtained by IANB and GGMB nerve blocks.